Hubungan Antara Kepribadian Agreeableness Dengan Kinerja Karyawan Di Pt. Haleyora Power Singkarak Sumatera Barat - Elvia Mun Nanda; Herio Rizki Dewinda; Isna Asyri Syahrina (Psyche 165 Journal, 2020)
The study aims to determine the relationship between personality Agreeableness and employee performance at PT. Haleyora Power Singkarak, West Sumatra. The independent variable in this study is personality Agreeableness and the dependent variable is Employee Performance. The measuring instrument used in this study is the personality Agreeableness scale and Employee Performance scale. The sampling technique in this study used a saturated sample technique. The sample in this research is 40 employee in PT. Haleyora Power Singkarak, West Sumatera. Validity and reliability test in this study using Alpha Cronbach technique. The results of the validity coefficient on the personality Agreeableness scale move from rix = 0.316 to 0.733, with a reliability coefficient of α = 0.873, while the Employee Performance Scale moves from rix = 0.362 to 0.770, with a reliability coefficient of α = 0.932. Based on data analysis, the value of the correlation between personality Agreeableness and the employee's performance is 0.556 with a significance level of 0,000. The results of the analysis of the effective contribution of the personality Agreeableness variable to employee performance were 31%.